RETRACTION NOTICE TO : Perangkat Lunak Perhitungan Perubahan Jabatan Dengan Menggunakan Fuzzy Analytical Hierarchy Process (Studi Kasus : UIN Sunan Ampel Surabaya) - Ilham Ilham (Systemic: Information System and Informatics Journal, 2017)
RETRACTED from SYSTEMIC due to DOUBLE PUBLICATION / DOUBLE SUBMISSION with article in QUERY: JOURNAL OF INFORMATION SYSTEMS Volume 1 number 1, April 2017. To read the article, follow http://jurnal.uinsu.ac.id/index.php/query/article/view/634